Exploration on the Construction of Central Legal Services District - Ruan, Xiaoying; Chen, Songyuan (International Journal of Social Sciences and Public Administration, 2024)
The construction of the Central Legal District has risen from regional exploration to institutional innovation at the national level. Yet research on more than ten Central Legal Services District  across the country has revealed that there exist such striking problems as prominent homogeneity of high-level planning; limitations for the providing of legal services; Imbalanced allocation of legal resources, and mediocre quality of legal services, etc.. On this basis, suggestions are proposed to strengthen the construction of legal districts and build superior legal affairs centre. Specifically, strengthening system planning and optimizing the layout of Central Legal Services District ; pooling efforts for the development of legal districts by collaborative innovation mechanism; utilizing talent advantages and expanding diverse supply entities; providing precise legal services by offering a comprehensive list of service items; and finally, strengthening institutional construction to improve work security mechanisms.